Climate neutrality requires coordinated measures for high quality recycling - Sun Xi; Frederik Lettow; Karsten Neuhoff (DIW Weekly Report, 2021)
For Europe to reach climate neutrality by mid-century, it needs to move toward a circular economy. Waste avoidance, reuse, and recycling save primary resources and avoid emissions in the production of basic materials like steel, cement, and plastics. Without exploring circular economy potentials, switching production to climate-neutral processes alone would result in significant costs and tremendous demand for clean energy. However, enabling the circular transition requires coordinated policy measures. Carbon costs must be fully reflected in basic material prices, while product standards and stakeholder incentives should be aligned with the recyclability of products. In addition, consumer awareness should be raised through reliable information on product environmental impacts, while investment in sorting and recycling infrastructure should be stimulated. Clear targets and definition of responsibilities are necessary for the effective implementation of these measures.
Keywords: Q53; Q54; Q58; L65; L51; H23; 330; industrial decarbonization; plastic recycling; circular economy; value chain; policy package